New Reagents and Synthetic Approaches to the Appel Reaction - S. C. de Andrade, Vitor; C. S. de Mattos, Marcio (Current Organic Synthesis, 2015)
The conversion of alcohol to alkyl halide in the presence of triphenylphosphine and carbon tetrahalide, which is commonly known as the Appel reaction, is an important route for halogenations under mild and neutral conditions. During the past twenty years, the Appel reaction has experienced a considerable evolution. Several convenient reagents have been developed and applied as electrophilic halogen sources despite a decline in the use of carbon tetrahalides. In addition, modified Appel-type reactions allow for the synthesis of alkyl halides as well as thiocyanates, nitrates, nitrites, amides, esters and acyl halides. Different synthetic methodologies to reduce the byproduct waste from the Appel reaction have been reported in the literature and are presented in this paper. Herein, this review will present recent achievements in the use of novel reagents and synthetic procedures for Appel-type reactions
Keywords: halogenation